Single‐Handed Double Helix and Spiral Platelet Formed by Racemate of Dissymmetric Cages. Issue 27 (26th May 2021) - Liu, Xiaoning; Shi, Zheng; Xie, Mingchen; Xu, Jianping; Zhou, Zhifan; Jung, Sinyeong; Cui, Guijia; Zuo, Yong; Li, Tao; Yu, Chunyang; Liu, Zhiqiang; Zhang, Shaodong
Abstract: Spontaneous deracemization has been used to separate homochiral domains from the racemic system. However, homochirality can only be referred to when the scales of these domains and systems are specified. To clarify this, we report self‐assembly of racemates of dissymmetric cages DC‐1 with a cone‐shape propeller geometry, forming a centrosymmetric columnar crystalline phase (racemic at crystallographic level). Owing to their anisotropic geometry, the two enantiomers are packed in a frustrated fashion in this crystalline phase; single‐handed double helices are observed (single‐handedness at supramolecular level). The frustrated packing (layer continuity break‐up) in turn facilitates screw dislocation during the crystal growth, forming left‐ or right‐handed spiral platelets (symmetry‐breaking at morphological level), although each platelet is composed of DC‐1 racemates. The symmetry correlation between DC‐1 molecules, the crystalline phase and spiral platelets, all exhibit C3 symmetry. Abstract : Hierarchical self‐assembly of dissymmetric cage DC‐1 forms an unusual supramolecular double helix, which is composed of six racemic pairs of DC‐1 per turn, and exhibits a single‐handed helical sense. These single‐handed helices with frustrated packing further assembled into hexagonal crystals with screw dislocation, with symmetry‐breaking at morphological level.